CLASIFICATION OF PEAT WATER QUALITY IN GIAM SIAK KECIL BUKIT BATU BIOSPHERE RESERVE, PROVINCE OF RIAU - Sutapa, Ignasius Dwi Atmana (LIPI Press, 2015)
The unsolved problem in Riau Province was the availability of clean water, since the province is dominated with peat land. Around Giam Siak Kecil Bukit biosphere reserve area are several potential sources of surface water that can be used as source of raw water. The aim of this study was to assess the peat water quality out of selected sites within Tanjung Leban area using STORET method in order to find out its quality classification and to try to improve its quality using a jar test lab scale. Based on the preassessment over four locations, Air Raja River was selected for it had several characteristics such as the water color was reddish and homogenous, had no sediment, had relatively constant water flow throughout the year, and was located on the edge of the road. Yet there were people's daily activities at the body of the river i.e. bathing, washing, and toileting. Based on its physical quality, the peat water had color levels ranging from 462 to 503 TCU, stench, and sour taste. The non-metallic chemical test of the peat water resulted in showing that it had pH 3.52. The peat water also contained Coliform bacteria and E. coli as many as 70 and 630 col/100ml, respectively. After going through STORET method analysis, the total score was -26, which means it had C status the quality of pollutans of which was light. After several physical and chemical quality improvement efforts using jar test, water quality could be improved up to A class (zero score).